KOREKSI ATAS : PERSPEKTIF â€œONTOLOGIâ€ DALAM FILSAFAT ILMU (Telaah Atas Buku Filsafat Ilmu Tulisan Jujun S. Suriasumantri) - Ghafir, Abdul (Kopertais Wilayah X Jawa Tengah, 2018)
Each discipline of Sciences has a scope of discussion on the basis of epistemologyÂ which is the reference in the discussion. Something particular epistemology may be aÂ reference from some science or may be di erent epistemology. . However, the messageÂ to be conveyed by a particular science, should be di erent, at least in terms of the speciÂ€ cations and provisions applicable in that science, including in terms of theÂ terminology used. If this is ignored, it will cause confusion of understanding and inÂ turn the message to be delivered discipline does not reach the target, even it raisesÂ the problem. Moreover, between Philosophy and Science, there is clearly a signiÂ€ cantÂ epistemological di erence. If Philosophy departs from the spirit of contemplativeÂ thinking that is not legitimated with the involution of any discipline, in a free andÂ underserved discourse. While Science departs from certain rules, even depended on aÂ particular discipline. Â is means that speaking of Philosophy must be independent ofÂ any discipline, speciÂ€ cation and legitimacy context. Â is paper attempts to describeÂ some of the terms applicable in Philosophy of Sciences which should not haveÂ happened and is legitimate to be corrected, otherwise it can be interpreted to straightenÂ understanding. Namely the use of the term â€œPhilosophyâ€ which is qualiÂ€ ed by theÂ term â€œScienceâ€ and the term â€œontologyâ€ on the book Philosophy of Science (A PopularÂ Introduction), by Jujun S. Suriasumantri published by: Pustaka Sinar Harapan, Jakarta,Â 1996.